The Legal Implications of Artificial Intelligence in Criminal Justice: From Surveillance to Sentencing - Md Shodiq; Rina Farah; Nurul Huda (Yayasan Adra Karima Hubbi, 2026)
Background. The increasing integration of Artificial Intelligence (AI) in criminal justice systems has raised significant concerns regarding its legal implications, particularly in surveillance and sentencing practices. As AI technologies become more embedded in law enforcement and judicial decision-making, questions surrounding privacy, accountability, and fairness have become central to discussions of legal reform. Purpose. The study aims to evaluate the extent to which current legal frameworks can address these challenges and propose reforms to ensure ethical use of AI in criminal justice systems. Method. A qualitative methodology is employed, using semi-structured interviews with legal experts, policymakers, and AI practitioners, alongside secondary data from case studies and policy documents. Results. The findings indicate that while AI has the potential to enhance efficiency, it often perpetuates existing biases and lacks sufficient oversight, leading to unjust outcomes. Conclusion. The study concludes that robust legal frameworks are essential to prevent the misuse of AI in criminal justice and to protect fundamental rights. This research contributes to the growing body of literature on AI's intersection with law and offers practical recommendations for legal reforms.